ANALISIS BUTIR SOAL BUATAN GURU MEKANIKA TEKNIK SEMESTER GANJIL KELAS X DI SMK N 5 PADANG - Irensia Purnama Sari; Oktaviani, ST, MT (CIVED, 2019)
Abstract– This research is motivated by the number of student who have not met the standards of KKM in Technical Mechanics. One of the factors causing the low value of students is the quality of the task is not good. This research aimed to investige the quality at items of task that already made by the teacher’s to the final exam for the Technical Mechanics subject in grade X of SMK N 5 Padang in the 2018/2019 in term of validity, reliability, difficullty index, discrimination index and distractor function. The data were colleced through documentation. The results of the calculation and analysis were as follows: 55% of the items valid; moderate reliability because the coefficient was 0,616; in terms of difficulty level of 20% is easy, 65% is mederate, and 15% is difficult; in the of discriminat of 70% is poor discrimination, 20% is moderately good discrimination, and 10% is good discrimination and in term of distractor function, 20% is very well functioning, 25% is well functioning, 35% is relatively well functioning, 15% is relatively poor, and 5% is poor functioning. The whole task of final exam for the Technical Mechanics subject in grade X of SMK N 5 Padang in the 2018/2019 academic year was in general in the moderately good category.Keywords: Tes Item Analysis, Technical Mechanics